Analysis of the Impact of System Deployment on the Digital Transformation of Supply Chain - Xu, Hao (Economics and Management Innovation, 2025)
Digital transformation of the supply chain is one of the core strategies for enterprises to enhance their market competitiveness, and in this process, system deployment plays an important role, directly determining the efficiency and adaptability of supply chain operations. System deployment includes the construction and execution of technical architecture, as well as the integration of corporate culture and optimization of management processes. By building an efficient data integration platform and optimizing information flow transmission, it is possible to achieve real-time decision support and automation of business processes, thereby significantly enhancing the response speed and collaboration efficiency of the supply chain. This article provides an in-depth analysis of the various applications of system configuration in practical operations, revealing how technological innovation can drive deep changes in the supply chain value chain. To achieve efficient system deployment, it is necessary to rely on advanced technology, as well as internal organizational collaboration and cultural adaptation within the enterprise as support.